Combined Effect of Palladium Catalyst and the Alcohol to Promote the Uncommon Bis‐Alkoxycarbonylation of Allylic Substrates. Issue 6 (11th February 2022) - Olivieri, Diego; Tarroni, Riccardo; Della Ca', Nicola; Mancuso, Raffaella; Gabriele, Bartolo; Spadoni, Gilberto; Carfagna, Carla
Abstract: A chemoselective method for the carbonylation of allylic substrates CH2 =CHCH2 X (X=OAc, OC(O)CH2 CN, OPh, OEt, OC(O)OPh, OC(O)O i Bu, N(H)C(O)Ph, N(Ph)C(O)Ph, N(H)Boc, N(Ph)Boc, Ph, CO2 Bn, CN), leading to alkyl succinates with preservation of the X group, under Pd(II)‐catalyzed oxidative carbonylation conditions, has been developed. Our method shows a completely different inverse chemoselectivity with respect to the "classical" substitutive carbonylation of the allyl compounds, which is known to provide β, γ ‐unsaturated carbonyl derivatives through the formation of a π‐allylpalladium intermediate. An accurate study, carried out using allyl acetate as model substrate, allowed to maximize the selectivity in the envisioned 2‐CH2 X substituted succinates. The best catalyst is generated in situ by mixing Pd(TFA)2 (TFA=trifluoroacetate) and the N, N′ ‐di(anthracen‐9‐yl)butane‐2, 3‐diimine ligand. p ‐Benzoquinone was used as oxidant in presence of benzyl alcohol, which acts as a nucleophile and as a solvent, under 4 bar of CO at 20 °C. A combined effect of the ligand and the nucleophile, rationalized through DFT calculations, has been observed both in promoting the bis‐alkoxycarbonylation process and in preventing π‐allylpalladium‐mediated side reactions, allowing the attainment of succinate derivatives with moderate to good yields. Abstract : Easy, unexpected access to useful 2‐substituted succinates was achieved starting from various allyl derivatives, including allyl carbonates, under mild conditions. The selectivity of this Pd‐catalyzed oxidative Bis‐Alkoxycarbonylation is governed by the combined effect of the ligand (anthryl α‐diimine) and the nucleophile (benzyl alcohol). Mechanistic insights, based on DFT calculations, were proposed.